Elaboración de una guía multimedia en línea del grafiti mediante programación html5 y actionscript 2 para difundir el arte urbano en la ciudad de Latacunga durante el año 2014. - Pila Caiza, César Silvio (2016)
Graphic design as a profession, allows expressively communicate ideas, facts and values processed and synthesized in terms of form and communication, social, cultural, economic, aesthetic and technological factors. The multimedia design is currently widely used due to its effectiveness to attract attention and convey different ideas in multimedia. the thesis topic "Development of an online multimedia guide GRAFFITI programmatically HTML5 and ActionScript 2 TO SPREAD THE URBAN ART IN THE CITY DURING THE YEAR 2014 LATACUNGA" emerged as a source of support that strengthens information and had graffiti as intended to encourage the population to assess the urban art through technological support and improve the company's relationship with the protagonists of this art, while giving space to set forth their ideas, feelings, emotions, where they feel conforming paint. Developmental inductive and analytical methods which were the basis to analyze and solve research were used, the research had a descriptive, enabling field and collect bibliographic data, characteristics and location information; observation techniques, survey and interview allowed to view and collect information through a questionnaire were used. For the preparation of the proposal as a final product of this work, a multimedia guide was designed whose content is intended to convey the history, culture and art where you can appreciate the graffiti and use new technologies for the dissemination and promotion of the same . By using this guide, the people who use it may incorporate references related to graffiti, thus benefiting young people aged between 18 and 30 interested in this urban art in the city of Latacunga.